Infants, children, and adolescents - Berk, Laura E (Pearson/Allyn and Bacon, 2005)
Includes bibliographical references (p. R1-R66) and indexes.; With a heightened emphasis on the interplay between biology and environment, and stronger focus on education (both at home and at school) and social policy as critical pieces of the dynamic system in which the child develops, Berk pays meticulous attention to the most recent scholarship in the field